O método vivo entre a estética literária e a sociomuseologia - Souza, Manoela Nascimento (2024)
The thesis consists of the development of an unprecedented method, the result of original theoretical and practical research, which is based on the theoretical connection between literary aesthetics and Sociomuseology. The name Living Method is the conscious and participatory process regarding the movement of the human world, which accompanies the freedom of thought and is located between experience and the socio-museological, between art and the scientific, between the practical and the theoretical, with a form to understand social movement in context and consequently trigger new movements. The connection between literary aesthetics and Sociomuseology appears to be innovative and fruitful considering the mutual development of the fields in the construction of this methodology. The theoretical foundation of the Living Method is due to the recovery of the Neoplatonic cosmological dialectic and the Hegelian dialectical movement in the contemporary socio-museological context and poetically metaphorized as part of this museological philosophical foundation in the movement of the literary aesthetic expression of the concept of feminine in two artists from different contexts, Florbela Espanca and Adriana Varejão, in understanding the logical movement of life-death-new, of generation, destruction and recreation; where the influence of the context as an aesthetic of displacement in the works is explained, and how the understanding of a movement encourages new movements and social transformations.